Pelatihan Pengolahan Data Menggunakan Software Statistik - Auliana, Rini Adriani; Dinda Puspita Ayu, Baiq; Ambang Lestari, Ayu; Nadia Nirwana, Baiq; Chothibul Umam Assa’ady, M (Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Students must have statistical knowledge because they need statistical knowledge to compile research data that has been conducted. The importance of understanding statistics and understanding statistical software, it is necessary to conduct training for students of the Faculty of Economics and Business, Bumigora University. The purpose of this training activity is students to be able to understand how to use various statistical software consisting of SPSS, SmartPLS and Eviews. The method used starts from planning, implementation and evaluation. The results of data processing training using statistical software SPSS, Eviews, and SmartPLS are very useful for students. The enthusiasm of students in this training was also very visible with the number of participants who attended the seminar and the enthusiasm of students to ask questions to the speakers. In addition, many positive reviews were also obtained from seminar participants and the enthusiasm of participants to take part in statistical training again.